1990
DOI: 10.1042/bj2650461
|View full text |Cite
|
Sign up to set email alerts
|

Collagen synthesis by cultured rabbit aortic smooth-muscle cells. Alteration with phenotype

Abstract: Enzymically isolated rabbit aortic smooth-muscle cells (SMC) in the first few days of primary culture express a 'contractile phenotype', but with time these cells modulate to a 'synthetic phenotype'. Synthetic-state SMC are able to proliferate, and, provided that they undergo fewer than 5 cumulative population doublings, return to the contractile phenotype after reaching confluency [Campbell, Kocher, Skalli, Gabbiani & Campbell (1989) Arteriosclerosis 9, 633-643]. The present study has determined the synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
68
0
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(75 citation statements)
references
References 74 publications
3
68
0
3
Order By: Relevance
“…[33] Our qualitative and quantitative study on the phenotypic expression of collagen has shown that cultured SMCs of the normal and diabetic Psammomys obesus synthesise more type I than type III collagen, in accord with the results of Layman et al [34] [36] have shown that SMC produced essentially collagen I and III. Ang et al [37] have observed an activation of mRNA coding 1 (I) and czl (III) chains of procollagen in rabbit synthetic SMCs. Compared with control, the diabetic state induced a large increase in type I and type III collagen biosynthesis and secretion. In addition, comparatively to collagen III, collagen I appeared more important in the medium (x10.8 vs x9.3) than in the cells (x13.6 vs x11.6).…”
Section: Discussionmentioning
confidence: 99%
“…[33] Our qualitative and quantitative study on the phenotypic expression of collagen has shown that cultured SMCs of the normal and diabetic Psammomys obesus synthesise more type I than type III collagen, in accord with the results of Layman et al [34] [36] have shown that SMC produced essentially collagen I and III. Ang et al [37] have observed an activation of mRNA coding 1 (I) and czl (III) chains of procollagen in rabbit synthetic SMCs. Compared with control, the diabetic state induced a large increase in type I and type III collagen biosynthesis and secretion. In addition, comparatively to collagen III, collagen I appeared more important in the medium (x10.8 vs x9.3) than in the cells (x13.6 vs x11.6).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been revealed that fibronectin and collagen promote arterial calcification 32) and that elastin, or laminin, inhibits such calcification 33,34) . We have previously reported that elastic fiber-related proteins, TE, fibrillin-1, and Lysyl oxidase, are suppressed by the induction of vascular calcification in cultured BASMCs 12) and the addition of recombinant tropoelastin significantly inhibits arterial calcification via 67 kDa elastin-binding protein (EBP) 15) .…”
Section: Discussionmentioning
confidence: 99%
“…The transient nature of the decorin effect on cell cycle-regulatory proteins may be due instead to the neutralization of decorin by binding to other matrix components, such as fibronectin and collagen, 25,62 because these ECM components are produced in large amounts in ASMCs. [63][64][65] Alternatively, the deposition of ECM molecules, such as fibronectin and collagen, may influence the proliferative response of ASMCs to growth factors 47,66 and override the effects of decorin on cell proliferation. For example, Koyama et al 47 demonstrated that ASMCs grown on fibrillar collagen had increased levels of cyclin-dependent kinase inhibitors and a decreased growth response to PDGF compared with cells cultured on monomeric collagen.…”
Section: Discussionmentioning
confidence: 99%